Autologous Hematopoietic Stem Cell Transplantation for Behçet’s Disease: A Retrospective Survey of Patients Treated in Europe, on Behalf of the Autoimmune Diseases Working Party of the European Society for Blood and Marrow Transplantation - Puyade, Mathieu; Patel, Amit; Lim, Yeong Jer; Blank, Norbert; Badoglio, Manuela; Gualandi, Francesca; Ma, David D.; Maximova, Natalia; Greco, Raffaella; Alexander, Tobias; Snowden, John A. (Frontiers in Immunology, 2021)
Background: Behçet’s Disease (BD) is an autoimmune disease mostly presenting with recurrent oral and genital aphtosisaphthosis, ulcers, and uveitis. PRare patients are rarely refractory to conventional immunosuppressive treatments. Autologous hematological hematopoietic stem cell transplantation (AHSCTaHSCT) is a standard of care in other autoimmune diseases. Some patients with BD have been treated with AHSCTaHSCT based on compassionate use. Objectives: Evaluate the outcome of AHSCTaHSCT in adult patients with BD treated in member centers of the European Society for Blood and Bone Marrow Transplantation (EBMT). Methods: Adults who received AHSCTaHSCT primarily for BD were identified retrospectively in the EBMT registry and/or in published literature. Data were extracted from either medical records of the patient or from publications. Results: Eight out of 9 cases reported to the registry and extracted data of 2 further patients from literature were analyzed. Four were female, median age at onset of BD was 24y (range 9-50). Median age at AHSCTaHSCT was 32y (27-51). Patients had received median 4 (2-11) prior previous lines of therapy (89% corticosteroids, 50% methotrexate, anti-TNFtherapy or cyclophosphamide). All patients had active disease before mobilization. Conditioning regimen was heterogeneous. Median follow-up was 48 months (range 6-240). No treatment-related mortality was reported. This procedure induced complete remission (CR) in 80%, partial remission in 10 % and lack of response in 10% of the patients. At last follow-up, one patient did not respond, 3Relapse rate was 30 % (2 relapses in patients in CR and 1 relapse in the patient in PR) with patients relapsed with pan-uveitis (n=1), aphtosisaphthosis (n=2) and arthralgia (n=1). Six patients were in CR. No late complications were reported. Conclusion: AHSCTaHSCT has an acceptable safety profile and represents a feasible and relatively effective procedure in severe and conventional treatment-resistant cases of BD is feasible and safe in multi-refractory patients with BD and has the potential to stabilize BD in patients with life-threatening involvements.